Brugada Syndrome Caused by Autonomic Dysfunction in Multiple Sclerosis - Michel Ibrahim; Garly Saint-Croix; Rosario Colombo (Case Reports in Cardiology)
Only one case report has previously described a patient with multiple sclerosis and a type 1 Brugada pattern on the electrocardiogram. Patients with multiple sclerosis have several neurological deficits including sensory symptoms, acute or subacute motor weakness, gait disturbance, and balance problems that may lead to an increased risk of falls. Concurrent autonomic dysfunction and neurologic consequences of multiple sclerosis may precipitate both mechanical falls and falls with loss of consciousness. While mechanistically different, the type 1 Brugada pattern presents similarly with syncope due to an insufficient cardiac output during dysrhythmia. In such patients, intracardiac defibrillators have shown to prevent sudden cardiac death in patients with the Brugada syndrome. In light of these similarly presenting but unique clinical entities, MS patients who develop a syncopal event in the setting of a spontaneous type I Brugada pattern pose a diagnostic and therapeutic dilemma. This case illustrates an approach to the risks and benefits of an ICD placement in an MS patient with the type 1 Brugada pattern.